An overview of reactive arthritis. Issue 7 (July 2019) - Pennisi, Megan; Perdue, Jacqueline; Roulston, Tessa; Nicholas, Joyce; Schmidt, Eric; Rolfs, Jenna
Abstract : ABSTRACT: Reactive arthritis, also known as Reiter syndrome, is a spondyloarthropathy that typically follows a urogenital or gastrointestinal infection, and is characterized by conjunctivitis, urethritis, and arthritis. The frequency of reactive arthritis in the United States is estimated at 3.5 to 5 patients per 100, 000. Physician assistants (PAs) can manage the condition; therefore, they should be familiar with the disease's signs and symptoms, diagnostic criteria, and treatment regimens. Without proper management, reactive arthritis can progress to a chronic destructive arthritis. Prompt recognition of the condition is key to early intervention and a better patient outcome with fewer complications.